INDONESIAN EFL STUDENTS’ WRITING ANXIETY IN POST-PANDEMIC ONLINE CLASSROOM CONTEXT: A SURVEY - Fina Sulfiana; Nia Kurniawati; Dahlya Indra Nurwanti (Institut Agama Islam Negeri (IAIN) Bone, 2022)
ESL and EFL students consider writing as challenging in both cognitive and affective aspects. In ideal circumstances, they may suffer from difficulties during the writing process, including anxiety or even tension. Furthermore, the COVID-19 pandemic condition has made the teaching and learning writing more complicated due to limited time and space to meet, to discuss, to collaborate, and to give as well as take feedbacks for their writing. Therefore, this study aims to investigate the types of writing anxiety experienced by EFL students in online Creative Writing class during the COVID-19 pandemic in Indonesia context. The research utilizes a quantitative method, specifically a survey technique. The online survey is administered to 124 participants of English Education Department at the fourth semester. To assess the levels and types of writing anxiety, the Second Language Writing Anxiety Inventory (SLWAI) established by Cheng (2004) was utilized in this study. The SLWAI was the first reliable instrument for assessing writing anxiety, particularly in a second or foreign language context. The results of this study show that the most common type of participants' writing anxiety is Avoidance Behavior (66.13%) then followed by Cognitive Anxiety (20,97%), and Somatic Anxiety (12.90%) as the minor type. The Avoidance Behavior type includes behavioral components of anxiety, such as the avoidance of writing. In conclusion, students of Avoidance Behavior type with have a normal level of nervousness since they seek to avoid writing situations. This study suggests that school teachers be more prepared to create online writing classroom atmosphere.